Knowledge and attitude on utilisation of infection prevention guidelines among nursing students of Mufulira and Kitwe schools of nursing - Kaluba Cedar (Lusaka, the university of Zambia, school of medicine, 2016)
Infection in healthcare facilities is a major public health problem problem in most developing countries like Zambia. Infection prevention guidlines are paramount in prevention of hospital acquired infections affording both patients and health workers protection from acquiring preventable infections.
Dissertation submitted in partial fulfilment for the award of bachelors degree in nursing sciences at the university of Zambia.
Includes bibliographic references.
Keywords: Infection-Prevention.